Feasibility of the Booklet on Female Reproductive System Material Based on the Inventory of Traditional Postpartum Medical Plants - Klaudia Mareta Sandra; Ruqiah Ganda Putri Panjaitan; Eko Sri Wahyuni; Shokhan Sharif Ali (Jurnal Pendidikan Sains Indonesia, 2026)
The learning process that takes place in the classroom utilizes educational media as an intermediary for delivering learning material, ensuring it is comprehended by the students. Educational media must be carefully selected and determined to achieve high-quality learning. The media used can be based on the integration of learning materials with research findings. The objective of this study is to assess the feasibility of a booklet on the female reproductive system as a learning media. This booklet contains an inventory of traditional medicinal plants for postpartum care in Nanga Danau Village, Kalis Subdistrict, Kapuas Hulu District, West Kalimantan Province, Indonesia. The development follows Sugiyono’s development model, which consists of five stages: potential and problems, data collection, product design, design validation, and design revision. The validity of the booklet was obtained through content validation conducted by five validators. Content validity analysis was performed using Aiken’s V. The validation results show that the booklet learning media is highly valid with a score of 0.97. Specifically, the validation scores for the aspects of presentation were 1.00, content 0.93, and language 0.97. Therefore, this booklet learning media is deemed suitable for use as a learning tool.